Preparation method and application of shikonin-loaded nano sponge hydrogel

By loading cyperin in nanosponge hydrogels and combining with high viscous hydrogels, the problem of poor bioavailability of existing cyperin preparations is solved, and a higher drug loading volume and longer drug release time is achieved, which significantly improves the therapeutic effect.

CN119656102APending Publication Date: 2025-03-21SHIHEZI UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411843429.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-14
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The active ingredient load of existing cyperin preparations is low and the bioavailability is poor, resulting in poor therapeutic effect.

Method used

By utilizing the three-dimensional cross-linked structure and porous structure of nanosponge, combined with high viscosity hydrogel, the loaded cyperin is stabilized and the sustained release effect is achieved through the action of the host and guest.

Benefits of technology

It improves the drug loading and bioavailability of cyperonin, extends the drug release time, enhances the therapeutic effect, and reduces the number of medications, and promotes wound healing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119656102A_ABST
    Figure CN119656102A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of nano sponge hydrogel loaded with alkannin. Beta-cyclodextrin and a BTDA cross-linking agent are subjected to cross-linking reaction through esterification reaction to prepare cyclodextrin nano sponge with a porous structure, and alkannin is stably loaded in the cyclodextrin nano sponge through subject-object interaction; the loading capacity of the alkannin can be improved, the slow release effect of the alkannin can be improved, and the drug release time can be prolonged; according to the present invention, the shikonin is used as a main body and is combined with the gel formed by the QCS and the PVA, and the adhesion with the skin is increased by using the high-viscosity hydrogel, such that the long-time pasting on the skin can be used, the slow release effect can be further improved, the shikonin bioavailability can be improved, the treatment effect can be improved, the drug use frequency can be easily reduced, and the secondary injury of the wound can be avoided; the wound healing can be better promoted. The preparation method disclosed by the invention is simple to operate and low in cost, has good stability and biocompatibility, and can remarkably improve the capability of promoting wound healing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogel preparation, and in particular to a preparation method and application of a shikonin-loaded nano sponge hydrogel. Background Art

[0002] Skin damage is an extremely complex skin disease caused by many factors such as physics, chemistry, sunlight, and radiation acting on the body, such as burns, skin trauma, sunburn, tumor radiotherapy burns, laser surgery burns, diaper dermatitis in children, skin bedsores, skin herpes zoster, acne, etc. As the largest organ in the human body, the skin plays an important role in protecting the body from damage and microbial invasion and maintaining body fluids, electrolytes, and nutrients. Once the skin has serious defects, it will lose its protective function. Wounds that cannot heal will not only increase the patient's pain and discomfort, but also increase the risk of amputation and medical expenses, causing serious physical, psychological and economic burdens on patients.

[0003] Lithospermum officinale is a perennial herbaceous plant of the Boraginaceae family, and "Shennong's Herbal Classic" records that its nature and flavor are sweet, salty, cold, with cooling blood, promoting blood circulation, detoxification, the effects of rash, curing blood heat toxicity, maculopapular purple black, measles not penetrating, sores, eczema, water and fire burns, can be taken orally or externally. Shikonin is one of the main active ingredients in Lithospermum officinale, with anti-inflammatory, analgesic, antibacterial, antiviral, antitumor, immunomodulatory, anti-fertility, liver protection, hemostasis and promotion of wound healing and other pharmacological effects. However, shikonin is a fat-soluble active substance, and water solubility is relatively low, and bioavailability is relatively poor, such as the common Lithospermum officinale preparations for skin diseases, Lithospermum officinale ointment, Lithospermum officinale muscle cream, etc., mostly are the ointments of oily bases, but the loading capacity of most effective active ingredients (shikonin) is low, and the drug sustained release effect is poor, and the drug release time is short, and the bioavailability is low, thereby limiting the therapeutic effect.

[0004] Therefore, it is necessary to develop new dosage forms for shikonin to improve its bioavailability. Summary of the invention

[0005] Therefore, based on the above background, the present invention provides a method for preparing a nanosponge hydrogel loaded with shikonin and its application, which utilizes the three-dimensional cross-linked structure and porous structure of the nanosponge and stably loads shikonin thereon through the host-guest interaction, which can not only increase the drug loading amount of shikonin, but also have a sustained-release effect, and is combined with the use of high-viscosity hydrogel to increase the adhesion to the skin, which can not only be attached to the skin for a long time, but also further improve its sustained-release effect, improve the bioavailability of shikonin, and improve its therapeutic effect.

[0006] The technical solution of the present invention is:

[0007] A method for preparing a nanosponge hydrogel loaded with shikonin comprises the following steps:

[0008] S1: dissolving β-cyclodextrin in an organic solvent, adding a cross-linking agent under stirring to react; treating the reaction product to obtain cyclodextrin nanosponge powder;

[0009] S2: uniformly dispersing the cyclodextrin nanosponge powder prepared in step S1 in water to obtain a suspension;

[0010] and dissolving shikonin in anhydrous ethanol to obtain a shikonin solution;

[0011] S3: adding the shikonin solution prepared in step S2 to the suspension in step S2, mixing, and treating the mixed solution to prepare shikonin cyclodextrin nanosponge powder;

[0012] S4: taking chitosan quaternary ammonium salt and polyvinyl alcohol, adding them into a solvent to dissolve them, and then mixing them evenly to prepare a blank hydrogel;

[0013] S5: dissolving the shikonin cyclodextrin nanosponge powder prepared in step S3 in ultrapure water to prepare a suspension, and then adding the suspension to the blank hydrogel in step S4, stirring and mixing to obtain a shikonin-loaded nanosponge hydrogel.

[0014] Further, the cross-linking agent in step S1 is selected from one of 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride and 4,4'-biphenyl ether dianhydride;

[0015] The molar ratio of the β-cyclodextrin to the cross-linking agent is (0.1-1.5): (6-12);

[0016] Preferably, the molar ratio of the β-cyclodextrin to the cross-linking agent is 1:(6-12).

[0017] Furthermore, the operation of treating the reaction product in step S1 is as follows:

[0018] After adding ultrapure water to the reaction product, filtering is performed, and after collecting the filtered solid, drying, grinding, impurity removal are performed in sequence, and then drying is performed to obtain cyclodextrin nano sponge powder.

[0019] Furthermore, the weight ratio of shikonin to cyclodextrin nanosponge powder in step S2 is 1:(1-20).

[0020] Furthermore, the treatment operation of the mixed solution in step S3 is as follows:

[0021] After removing the ethanol from the mixed liquid, the mixture was centrifuged, and the supernatant was freeze-dried to obtain shikonin cyclodextrin nanosponge powder.

[0022] Furthermore, the dosage ratio (by weight) of the chitosan quaternary ammonium salt and the polyvinyl alcohol in step S4 is 1:(1-3).

[0023] Further, in step S5, the shikonin cyclodextrin nanosponge powder prepared in step S3 is dissolved in ultrapure water to prepare a suspension with a concentration of (3-6) w / v%;

[0024] The blank gel and the suspension were stirred and mixed in a volume ratio of (2-5):1 to obtain a nanosponge hydrogel loaded with shikonin.

[0025] Based on the same inventive concept, the present invention also provides a shikonin-loaded nanosponge hydrogel prepared by the above-mentioned method for preparing a shikonin-loaded nanosponge hydrogel.

[0026] Based on the same inventive concept, the present invention applies the shikonin-loaded nanosponge hydrogel prepared by the above-mentioned method for preparing a shikonin-loaded nanosponge hydrogel to the preparation of drugs for skin damage.

[0027] Furthermore, the skin damage includes burns, mechanical damage, sunburn, tumor radiotherapy burns, laser surgery burns, and damage caused by diaper dermatitis, skin bedsores, skin herpes zoster or acne.

[0028] The beneficial effects achieved by the technical solution of the present invention are:

[0029] The present invention uses an esterification reaction to cross-link β-CD (β-cyclodextrin) with a cross-linking agent to prepare a cyclodextrin nanosponge with a porous structure, and stably loads shikonin therein through hydrogen bond interaction and electrostatic adsorption, which can not only increase the effective amount of shikonin, but also improve its sustained release effect and prolong the drug release time;

[0030] The present invention combines a cyclodextrin nanosponge with a high load of shikonin with a gel formed by QCS (quaternary ammonium salt of chitosan) and PVA (polyvinyl alcohol), and utilizes the highly viscous hydrogel to increase the adhesion to the skin, so that the sponge can be attached to the skin for a long time, and its sustained release effect can be further improved, the bioavailability of shikonin can be improved, the therapeutic effect can be improved, and the number of medications can be reduced, so that secondary damage to the wound site can be avoided, and wound healing can be better promoted.

[0031] The preparation method of the present invention is simple to operate, low in cost, has good stability and biocompatibility, and can significantly improve the ability to promote wound healing. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Attached Figure 1Transmission electron micrographs of CDNS (A) and CDNS-SHI (B) of Example 1, and scanning electron micrograph of CDNS-SHI@QCS-PVA hydrogel (C);

[0033] Attached Figure 2 The encapsulation efficiency of SHI in CDNS of Example 1, and the full-wavelength UV spectra of SHI, CDNS and CDNS-SHI;

[0034] Attached Figure 3 FT-IR graphs of β-CD, BTDA, a physical mixture of β-CD and BTDA, CDNS, SHI, and CDNS-SHI of Example 1;

[0035] Attached Figure 4 This is a graph showing the water retention of the CDNS-SHI@QCS-PVA hydrogel of Example 1 at 4°C and room temperature;

[0036] Attached Figure 5 The drug loading rate diagram of CDNS-SHI in Example 1 (A) and the cumulative drug release diagram of SHI and CDNS-SHI@QCS-PVA (B).

[0037] Attached Figure 6 The figure is the animal model of Example 2 (A), the wound healing figure from 1 to 14 days (B), the wound healing simulation figure (C), the body weight change figure (D), the wound healing area figure (E), and the wound healing rate figure (F). DETAILED DESCRIPTION

[0038] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with its embodiments; it should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0039] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0040] Shikonin (SHI, 98%, molecular weight: 288.299) was purchased from Chengdu Purui Technology Co., Ltd. β-Cyclodextrin (β-CD, 98% biotechnology grade, molecular weight: 1134.98), cross-linking agent, chitosan quaternary ammonium salt (QCS), polyvinyl alcohol (PVA), dimethyl sulfoxide (DMSO), and triethylamine (Et3N) were purchased from Shanghai MacLean Co., Ltd.

[0041] The technical solution of the present invention is:

[0042] A method for preparing a nanosponge hydrogel loaded with shikonin comprises the following steps:

[0043] S1: dissolving β-cyclodextrin in an organic solvent, adding a cross-linking agent under stirring to react; treating the reaction product to obtain cyclodextrin nanosponge powder;

[0044] In this step, when β-cyclodextrin is dissolved in the organic solvent, heating is performed, and the heating temperature is controlled at 50-90° C., preferably 80° C.; the stirring time is 5-30 min, preferably 25 min.

[0045] The cross-linking agent in this step is selected from one of 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 2,3,3',4'-biphenyltetracarboxylic dianhydride, and 4,4'-biphenyl ether dianhydride;

[0046] The molar ratio of β-cyclodextrin to the cross-linking agent is 1:(6-12),

[0047] Preferably, the molar ratio of the β-cyclodextrin to the cross-linking agent is 1:10.

[0048] The operation of treating the reaction product in this step is as follows:

[0049] After adding ultrapure water to the reaction product, the product is filtered and filtered to obtain the filtered solid, which is then dried, ground, and impurity-removed in sequence, and then dried to obtain cyclodextrin nanosponge powder (CDNS).

[0050] The impurities are removed by using a Soxhlet extractor with ethanol and ultrapure water as detergents;

[0051] The drying in this step is performed by vacuum drying.

[0052] S2: uniformly dispersing the cyclodextrin nanosponge powder prepared in step S1 in water to obtain a suspension;

[0053] and dissolving shikonin (SHI) in anhydrous ethanol to obtain a shikonin solution;

[0054] In this step, the weight ratio of shikonin to cyclodextrin nano-sponge powder is 1:(10-20), preferably, the weight ratio of shikonin to cyclodextrin nano-sponge powder is 1:15.

[0055] S3: adding the shikonin solution prepared in step S2 to the suspension in step S2, mixing, and treating the mixed solution to prepare shikonin cyclodextrin nanosponge powder (CDNS-SHI);

[0056] The treatment operation of the mixed solution in this step is as follows:

[0057] After removing the ethanol in the mixture, centrifugation is performed, and the supernatant is freeze-dried to obtain shikonin cyclodextrin nanosponge powder.

[0058] The centrifugation conditions were 8000 rpm, 4°C, and 10 min.

[0059] The freeze-drying conditions are -80℃ and pressure 0.1Kpa.

[0060] S4: Take chitosan quaternary ammonium salt (QCS) and polyvinyl alcohol (PVA), add them into a solvent, heat and dissolve them, and mix them evenly to prepare a blank hydrogel (QCS-PVA);

[0061] In this step, the dosage ratio (by weight) of chitosan quaternary ammonium salt and polyvinyl alcohol is 1:1.

[0062] The solvent in this step is a mixture of glycerol and water. Preferably, the weight ratio of glycerol to water is 3:1.

[0063] The heating temperature in this step was controlled at 37°C.

[0064] S5: dissolving the shikonin cyclodextrin nanosponge powder prepared in step S3 in ultrapure water to prepare a suspension, and then adding it to the blank hydrogel in step S4, stirring and mixing, to obtain a nanosponge hydrogel loaded with shikonin

[0065] In this step, the shikonin cyclodextrin nanosponge powder prepared in step S3 is dissolved in ultrapure water to prepare a suspension with a concentration of 6 w / v% (w / v% represents the mass percentage of the solute in 100 ml of the solution);

[0066] The blank gel and the suspension were stirred and mixed in a volume ratio of 3:1 to obtain a nanosponge hydrogel loaded with shikonin.

[0067] Embodiment 1:

[0068] 1) Anhydrous β-cyclodextrin (1.1350 g) was heated and dissolved in anhydrous DMSO (4 mL) containing 1 mL of anhydrous triethanolamine, and the heating was stopped. Under vigorous stirring conditions, the crosslinking agent BTDA was added to the solution at a molar ratio of β-cyclodextrin to the crosslinking agent of 1:10, and then a polymerization crosslinking reaction was carried out. The polymerization process was completed within a few minutes. After the reaction was completed, it was cooled to room temperature, 30 mL of ultrapure water was added, and a white precipitate appeared. It was filtered and then vacuum dried for 12 hours. After drying, the solid product was ground with a mortar, and washed with ethanol and ultrapure water in a Soxhlet extractor for 3 times. Finally, it was dried in a vacuum drying oven at 60° C. for 24 hours to obtain a product, namely cyclodextrin nanosponge powder (CDNS).

[0069] 2) Dispersing cyclodextrin nanosponge powder in ultrapure water and sonicating, adding shikonin to anhydrous ethanol at a weight ratio of shikonin to cyclodextrin nanosponge powder of 1:15 to obtain a shikonin solution; adding the shikonin solution to the cyclodextrin nanosponge powder suspension, mixing, removing ethanol from the solution by evaporation, and then stirring the solution at room temperature in the dark overnight, and then centrifuging at 8000 rpm for 10 minutes. Finally, freeze-drying the supernatant to obtain shikonin cyclodextrin nanosponge (CDNS-SHI).

[0070] 3) Pure water and glycerol were mixed thoroughly in a ratio of 3:1 as the solvent, 300 mg of QCS and 300 mg of PVA were weighed and added to the above solvent, and dissolved by heating in a water bath at 37°C. After mixing evenly, a blank hydrogel was obtained, and bubbles were removed by ultrasonication for 30 min, and the hydrogel was stored in a refrigerator at 4°C.

[0071] The shikonin cyclodextrin nanosponge powder was dissolved in ultrapure water to prepare a suspension with a concentration of 6 w / v%, which was then added to the obtained blank hydrogel. The blank gel and the SHI-loaded CDNS suspension were stirred and mixed at a volume ratio of 3:1 to finally obtain a shikonin-loaded nanosponge hydrogel, which was then stored in a 4°C refrigerator for later use.

[0072] Next, the structural characteristics and performance of the intermediates and products in the preparation process of Example 1 were analyzed.

[0073] (1) By Figure 1 Transmission electron microscopy characterization pictures, Figure 1 (A) It can be clearly seen that the cyclodextrin nanosponge is a spherical structure with a porous structure inside; Figure 1 (B) Shikonin is round black particles. In the figure, black particles can be clearly seen in the cyclodextrin nanosponges, indicating that shikonin is successfully loaded into the cyclodextrin nanosponges; Figure 1 (C) The hydrogel has a three-dimensional network structure with high porosity and dense consistency.

[0074] Depend on Figure 2 The full-wavelength UV spectrum shows that SHI has a characteristic UV absorption peak at 516nm, while CDNS-SHI has a characteristic UV absorption peak of SHI at 516nm; Figure 3 The FTIR results showed that β-CD was -1 To 3008cm -1 There is a broad peak at 2821cm -1 There is a peak at 3693cm-1, which corresponds to the -OH stretching vibration peak and -CH stretching vibration peak of β-CD. -1 To 3182cm -1There is a broad peak in the range, which is narrower than the peak of β-CD. -1 and 1072cm -1 Two new peaks were formed at the β-CD, corresponding to the -C=C and -CO stretching vibration peaks. The reduction of -OH in β-CD and the newly formed ester bond proved the successful synthesis of cyclodextrin nanosponge. The physical mixture of β-CD and BTDA retained the characteristic peaks of -OH stretching vibration of β-CD and the characteristic peaks of -C=O, -C=C and -CO stretching vibration of the anhydride, indicating that the physical mixture of β-CD and the anhydride did not react. In the SHI spectrum, this absorption peak is at 2877cm -1 、1616cm -1 and 773cm -1 The positions correspond to =CH stretching vibration, C=C stretching vibration and =CH in-plane bending vibration, respectively, which is the trisubstituted olefin structure of SHI. This structure also has corresponding peaks in the CDNS-SHI spectrum, indicating that shikonin has been successfully loaded into the nanosponge.

[0075] (2) To investigate the water retention of CDNS-SHI@QCS-PVA, the hydrogels at different temperatures were weighed at 10:00 every day and the water loss was calculated. Figure 4 shown.

[0076] from Figure 4 It can be seen that CDNS-SHI@QCS-PVA is very stable at both 4°C and room temperature, and the water retention rate is still 99.82% and 99.63% after 14 days. When stored at 4°C, the hydrogel loses less water, indicating that the hydrogel is more stable when stored at 4°C.

[0077] (3) Determination of drug loading rate of shikonin nanosponges

[0078] An appropriate amount of CDNS was dissolved in ultrapure water, and SHI was dissolved in anhydrous ethanol. The above solutions were mixed in a ratio of CDNS to SHI of 1:1, 1:5, 1:10, 1:15, and 1:20, and were slowly stirred for 24 hours under dark conditions and then centrifuged (8000 rpm, 10 min). Then, the precipitate (unencapsulated SHI) was dissolved in anhydrous ethanol, and the absorbance intensity of SHI was detected at the maximum absorption peak λ=516 nm using ultraviolet-visible spectroscopy (UV-vis). The drug loading rate of CDNS to SHI in the sample was calculated according to the obtained linear regression equation. The drug loading rate calculation formula is as follows:

[0079] SHI loading rate (%) = SHI content in supernatant / SHI input amount × 100%

[0080] The drug loading rate of CDNS to SHI was calculated and the results are shown in Figure 5A, When the mass ratio of CDNS to SHI is 15:1, the drug loading rate is the highest, which is 73.02%.

[0081] (4) Determination of in vitro release

[0082] SHI and CDNS-SHI@QCS-PVA hydrogel (4 mL) were added to the pretreated dialysis bag, and 500 mL of PBS containing 0.1% Tween 80 was used as the medium with pH = 7.4, the temperature was controlled at (37 ± 0.5) °C, and the rotation speed was 250 r·min -1 , 2 mL of samples were taken at 0h, 0.5h, 1h, 2h, 4h, 6h, 8h, 12h, 24h, 36h, and 48h, and the isothermal and equal volume medium was added. The collected solutions were tested for the absorbance intensity of SHI and CDNS-SHI@QCS-PVA hydrogel using an ultraviolet spectrophotometer at the maximum absorption peak of SHI at λ=516nm. The concentration was calculated according to the in vitro release calculation formula, which is as follows:

[0083] In vitro SHI cumulative release rate % = (SHI release amount / total SHI amount) × 100%

[0084] Calculate the cumulative release of SHI, the results are shown in Figure 5 B, the cumulative release of SHI and CDNS-SHI@QCS-PVA hydrogels in 24 hours were 24.56% and 44.77%, respectively. The release of CDNS-SHI@QCS-PVA hydrogel was significantly higher than that of pure SHI. As can be seen from the figure, CDNS-SHI and CDNS-SHI@QCS-PVA hydrogels effectively prolonged the drug release time, indicating that CDNS-SHI@QCS-PVA hydrogel has a good sustained-release effect.

[0085] Example 2: Animal Experiment

[0086] Animal breeding environment

[0087] Barrier level: SPF level; temperature: 23±2℃; relative humidity: 50±10%; environmental noise: ≤60dB; provide sufficient feeding feed and drinking water.

[0088] Grouping and treatment of experimental animals

[0089] Experimental animal groups: 36 6-week-old SD male rats were equally divided into 3 groups, including a model group (control, n = 12), a blank hydrogel group (QCS-PVA, n = 12), and a cyclodextrin nanosponge hydrogel group loaded with shikonin (CDNS-SHI@QCS-PVA, n = 12). During the administration period, the health status and diet of the rats were observed daily, and the daily weight changes of the rats were recorded.

[0090] Establishment of full-thickness wound model: After 7 days of adaptive feeding, the newly purchased rats were weighed and the animal model was established. Before modeling, the rats should be fasted for 12 hours. 10% chloral hydrate solution was injected intraperitoneally to anesthetize the rats, and the dosage was 0.3 mL / g. The hair on the back of the rats was removed with an electric shaver, and the skin surface of the rats was wiped with saline. A medical punch biopsy instrument (1 cm) was used to punch holes symmetrically on the back to make full-thickness circular excision wounds. The day of modeling was regarded as day 0, and the skin wound surface was photographed and recorded. After punching, the rats were placed in a clean cage to recover on their own and were kept in a single cage to prevent the rats from biting each other's skin. Starting from the first day after modeling, the rats were given drugs every day at 11:00 am. When giving drugs, try not to pull the wound site to avoid secondary injury, and clean the cage at the same time. Skin tissue sampling was performed on the 7th and 14th days, and the skin wound surface was photographed on days 0, 4, 7, 11, and 14 to observe the wound healing.

[0091] A 14-day animal experiment process model diagram, the results are shown in Figure 6 (A) shown.

[0092] During the treatment period, the wound surface was photographed with a digital camera on days 0, 4, 7, 11, and 14, and the efficacy of the treatment was observed. The results are shown in Figure 6 (B) and 6(C).

[0093] From day 0 to day 14, the body weight of rats in different groups gradually increased, indicating that the treatments in different groups did not inhibit or reduce the body weight of rats. Figure 6 (D).

[0094] On the 14th day, the wounds in the drug-treated group were basically healed, but the CDNS-SHI@QCS-PVA hydrogel group was able to significantly promote healing. Figure 6 (EF).

[0095] The above is only a preferred embodiment of the present invention. For ordinary technicians in this technical field, for example, metal ions can be added to the nanosponge to make it pH responsive, or it can be combined with photothermal responsive materials to enhance the therapeutic effect.

Claims

1. A method for preparing a nanosponge hydrogel loaded with shikonin, characterized in that: It includes the following steps: S1: dissolving β-cyclodextrin in an organic solvent, adding a cross-linking agent under stirring to react; treating the reaction product to obtain cyclodextrin nanosponge powder; S2: uniformly dispersing the cyclodextrin nanosponge powder prepared in step S1 in water to obtain a suspension; and dissolving shikonin in anhydrous ethanol to obtain a shikonin solution; S3: adding the shikonin solution prepared in step S2 to the suspension in step S2, mixing evenly, and treating the mixed solution to prepare shikonin cyclodextrin nanosponge powder; S4: taking chitosan quaternary ammonium salt and polyvinyl alcohol, adding them into a solvent to dissolve them, and then mixing them evenly to prepare a blank hydrogel; S5: dissolving the shikonin cyclodextrin nanosponge powder prepared in step S3 in ultrapure water to prepare a suspension, and then adding the suspension to the blank hydrogel in step S4, stirring and mixing to obtain a shikonin-loaded nanosponge hydrogel.

2. The method for preparing a shikonin-loaded nanosponge hydrogel according to claim 1, characterized in that: The cross-linking agent in step S1 is selected from one of 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride and 4,4'-biphenyl ether dianhydride; The molar ratio of the beta-cyclodextrin to the cross-linking agent is (0.1-1.5): (6-12).

3. The method for preparing a shikonin-loaded nanosponge hydrogel according to claim 2, characterized in that: The operation of treating the reaction product in step S1 is as follows: After adding pure water to the reaction product, filtering is performed, and after collecting the filtered solid, drying, grinding, impurity removal are performed in sequence, and then drying is performed to obtain cyclodextrin nano sponge powder.

4. The method for preparing a shikonin-loaded nanosponge hydrogel according to claim 1, characterized in that: The weight ratio of shikonin to cyclodextrin nanosponge powder in step S2 is 1:(1-20).

5. The method for preparing a shikonin-loaded nanosponge hydrogel according to claim 1, characterized in that: The treatment operation of the mixed solution in step S3 is as follows: After removing the ethanol in the mixed solution, centrifugation is performed, and the supernatant is freeze-dried to obtain shikonin cyclodextrin nanosponge powder.

6. The method for preparing a shikonin-loaded nanosponge hydrogel according to claim 1, characterized in that: The dosage ratio (by weight) of chitosan quaternary ammonium salt and polyvinyl alcohol in step S4 is 1:(1-3).

7. The method for preparing a shikonin-loaded nanosponge hydrogel according to claim 1, characterized in that: In step S5, the shikonin cyclodextrin nanosponge powder prepared in step S3 is dissolved in ultrapure water to prepare a suspension with a concentration of (3-6) w / v%; The blank gel and the suspension were stirred and mixed in a volume ratio of (2-5):1 to obtain a nanosponge hydrogel loaded with shikonin. 8 . The shikonin-loaded nanosponge hydrogel prepared by the method for preparing the shikonin-loaded nanosponge hydrogel according to any one of claims 1 to 7 .

9. Use of the shikonin-loaded nanosponge hydrogel prepared by the method for preparing the shikonin-loaded nanosponge hydrogel according to any one of claims 1 to 7 in preparing a drug for skin damage.

10. The use according to claim 9, characterized in that: The skin injuries include burns, mechanical injuries, sunburn, tumor radiotherapy burns, laser surgery burns, and injuries caused by diaper dermatitis, bedsores, herpes zoster or acne in children.